(C6F5)3B·(HF)n-catalyzed glycosylation of disarmed glycosyl fluorides and reverse glycosyl fluorides. Issue 13 (26th April 2021) - Long, Qing; Gao, Jingru; Yan, Ningjie; Wang, Peng; Li, Ming
Abstract : (C6 F5 )3 B·(HF) n -catalyzed glycosylation of disarmed glycosyl fluorides and reverse glycosyl fluorides with structurally diverse nucleophiles has been achieved. Abstract : Glycosyl fluorides as glycosylating agents have been widely applied in constructing diverse glycosidic bonds, however, catalytic glycosylation of disarmed glycosyl fluorides is largely undeveloped. Herein, we describe catalytic (C6 F5 )3 B·(H2 O) n -initiated glycosylation of a wide range of disarmed glycosyl fluorides and reverse glycosyl fluorides with a variety of O - and C -nucleophiles. The reactions proceed smoothly under the mild reaction conditions and provide the desired glycosides in good-to-excellent yields. The transformations enjoy a broad substrate scope and accommodate the functional groups used frequently in carbohydrate chemistry. Preliminary mechanistic studies suggest that the adduct (C6 F5 )3 B·(HF) n, in situ generated from the ligand exchange of (C6 F5 )3 B·(H2 O) n with the HF delivered during the reaction, might be the actual catalyst in the reaction. The species represents a new Lewis acid-assisted Brønsted acid with enough acidity to effect catalytic glycosylation of disarmed glycosyl fluorides. Configuration-controlled one-pot synthesis of oligosaccharides is achieved based on difference in reactivity of β-glycosyl fluorides and their α-congeners relying on (C6 F5 )3 B·(HF) n catalysis.